Phonostylistics: concept and trends - Nodirova, Sevinch (The Lingua Spectrum, 2025)
The article explores the phonostylistics’ conceptual basis and also its historical growth as a separate field of linguistics. The article shows how phonics evolved - from the origins in ancient rhetoric and the first phonetic research to modern approaches, uniting different disciplines. An important aspect is how phonics combines the approaches of phonetics and stylistics to study expressive and emotional components of both oral and written speech. The importance of sound components in expressing the text’s semantic, affective, and aesthetic elements is taken into account. Particular focus is placed on the role that phonostylistic techniques play in speech expression, identification, and utterance pragmatics, as well as their functional load and creative speech. In this work, we discuss the most important sound features, such as intonation, rhythm, stress and phonemic opposition, and how they affect the creation of a language style. Attention is drawn to the importance of phonostilistic analysis in areas such as sociolinguistics, discourse analysis and speech interaction, and discusses the influence of phonostilistic characteristics on cultural and contextual elements.